Comparative Effects of Diazepam Infusion and Divided Doses of Diazepam on the Treatment of Absence Status Epilepticus - Karimzadeh, P.; Afshar khas, L.; Mosavat, A. (Iranian Journal of Child Neurology, 2009)
Objective Absence status epilepticus (ASE) is a common form of nonconvulsive status epilepcticus. It is characterized by loss of consciousness with spike and wave discharges in EEG simultaneously. The most effective treatment of ASE is diazepam, either infusion or in divided doses; the former is more expensive since patients must be admitted in an Intensive Care Unit. The aim of this study was to evaluate and compare the efficacy of diazepam infusion and parenteral diazepam in divided doses in the treatment of ASE. Materials & Methods This randomized controlled clinical trial, enrolled 20 patients with absence status epilepticus. Diagnosis was made based on the clinical manifestations and electroencephalogram (EEG). Prior to treatment, all patients underwent EEG and imaging. Patients were randomized to receive 0.2 mg/kg/h diazepam infusion or 0.2 mg/kg in six daily doses. Clinical and EEG improvements were considered to be optimal responses. Results Of the 20 patients studied, 13 (65%) were boys and the remaining 7(35%) were girls. There were no differences between the two groups regarding age and sex (non-significant). Following treatments after 48 hours, 1 week and 1 month respectively, clinical improvement in previous problems (loss of consciousness, ataxia, behavior and speech problems) and EEGs was similar in both groups (p=1). There were controlled seizures in 18 (90%), abnormal CT scans in 5 (25%), abnormal EEGs after treatments in 6 (30%) cases; however no significant differences were seen between the two groups. Conclusion This study demonstrates that there are no significant differences between treatments of ASE with diazepam infusion and parenteral diazepam in divided doses. Treatment of ASE, with divided doses of diazepam is easier, less expensive and patients do not require to be hospitalized in an Intensive Care unit.